Classes sociais e apropriação do espaço urbano na cidade de Anápolis,Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2021)
This research focuses on some of the consequences that inequality unleashes within the urban space. For this, we discuss the space, as well as the way it is conceived; and about the economy, as we believe that the current economic system is responsible for many of the evils present in today's society. Thus, we go through important themes, such as the construction of space, the fragmentation of knowledge that, wrapped up in the plot made by capitalism, ends up becoming an ally in the production and accumulation of capital, and the urban space of Anápolis, its distortions and contradictions. As we seek to elucidate the inequalities present in the city of Anápolis and the violence that resulted from them, we bring a series of photos and illustrations that demonstrate to the reader the unequal yoke that weighs for a large portion of the city population. The mere description of the urban space of Anápolis is enough to demonstrate that, in the first place, we do not know the city as it really is, because we create a routine that always makes us frequent a specific perimeter. Second, that our experience of the city is not an absolute truth, our conception of the city comprises only one among the various ways of experiencing it.
Social classes and appropriation of urban space in the city of Anápolis, Goiás
Keywords: Espaço urbano; Cidade; Desigualdades; Acumulação de capital; Urban space; City; Inequalities; Capital accumulation; CIENCIAS HUMANAS::EDUCACAO